Dampak Transformasi Wilayah terhadap Kondisi Kultural Penduduk (Tinjauan Perspektif Geografis) - Giyarsih, Sri Rum (Universitas Muhammadiyah Surakarta, 2012)
This research was conducted in Yogyakarta-Surakarta Corridor aiming at analyzing the impacts of regional transformation on the cultural life of the citizens. Method applied in this research is based on the survey technique, with 120 household has been taken as the sample. Sampling technique based on stratified random sampling has been implemented in 4 villages that represent different degrees of accessibility, namely: Maguwoharjo Village-Sleman Regency (very high accessibility), Sumopuro Village-Klaten Regency (high accessibility), Danguran Village-Klaten Regency (medium accessibility), and Jatirejo Village-Boyolali Regency (low accessibility). Analysis technique is taken based on the descriptive quantitative analysis. The findings of this study show us that regional transformation has impacts on citizens cultural condition in the forms of some changes in traditional practices of dealing with pregnancy, birth, transition from childhood to adult life, marriage, and death, from complex practices to simpler ones. In the geographical perspective, this research also reveal the spatial variation (based on the 4 type of the village that represent different degrees of accessibility) from the impact of regional transformation on the cultural life of the citizens.